PERSONAL DETERMINANTS OF READINESS FOR PFOFESSIONAL RISK OF SPECIAL DIRECTORS - Патруль, М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
This article theoretically analyzed and empirically confirmed the personal determinants of readiness for professional risk of employees of the special purpose division "Jaguar".The sample of the empirical research was the employees of the 8th separate special regiment "Jaguar".The study was carried out by three methods: 1) theoretical methods: analysis, synthesis, systematization, classification and generalization; 2) psychodiagnostic methods: testing - method of diagnosis of the degree of readiness for the risk of Schubert, the questionnaire "Personal factors of decision-making (LFP-25)" T.Kopnilov,style of self-regulation of behavior V. Mopocanova, Є. Konose,the questionnaire of the propensity to risk A. Shmelev,the questionnaire of self-relations V. Stolin, S. Panteleev,method "Personal aggressiveness and conflict" Є. Ilyin, P. Kovalev,method of diagnosis of personality on the motivation to avoid failures T. Elepca,method of diagnosis of personality on the motivation for success T. Elepca;3) static methods: the method of cognitive and regulatory analysis (criteria of Spirman).The practical significance of this study is the ability to use materials and conclusions in the further study of the problem of readiness for professional risk; in the development of targeted programs to minimize the negative psychological consequences of the activities of employees of special purpose subunits in special conditions and critical situations;to enhance the effectiveness of activities in the process of determining the behavior of workers of special purpose; when preparing a personality for professional activities in special purpose units.